Akad Sharf Dalam System Jual Beli Valuta Asing (Valas) - Muhammad W, Syafaat; Sakti, Salwa Nurfauziyah; Masse, Rahman Ambo; Asapa, Nasrullah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Bai’ as-sharf or the practice of exchanging foreign currencies (forex) from an Islamic legal standpoint is a relevant issue due to the rapid growth of Islamic economics. Currency exchange has become a common need among people. It arises from basic demands when trading across borders or staying in foreign countries. Since such transactions involve the exchange of money for money, which falls under the category of usurious items, it is important to examine the Islamic stance on this matter. Several types of forex or sharf transactions are prevalent, including spot, forward, swap, and option. However, it is essential to distinguish which of these are deemed permissible in Islamic finance and which are not, along with the justifications.